Marriage decline rate phenomenon in indonesia and its relevance to marriage encouragement in islam - Arwa Sya’ima; Widiyanto; Zainal Arifin (Yayasan Azhar Amanaa Yogyakarta, 2024)
This research examines the phenomenon of declining marriage rates in Indonesia and its relevance to the recommendation of marriage in the perspective of the Qur'an and Hadith. Data from the Central Statistics Agency shows a decrease in marriages over the last 6 years by 438,916 marriages. The causes are social, economic, and psychological factors, such as a free lifestyle, a focus on career advancement, unstable financial conditions, pursuing education, divorce trauma, egocentrism, and despair in finding a partner. A review of QS. An-Nur (24): 32-33 and Hadith Bukhari No. 5066 shows that the recommendation to marry aims to channel desire through the means permitted by Allah and to avoid the act of fornication. Delaying marriage in Indonesia does not contradict the recommendation to marry as long as the youth can refrain from the act of fornication. However, marriage has a more noble meaning than just the release of desire, which is the realization of sakinah, mawaddah, rahmah, and the perfection of half of one's religion. It is suggested that policymakers assist the younger generation who delay marriage by providing them with provision, training, capital, and post-marriage guidance.